Tasks of Public Relations Officer at RSND during COVID-19 Pandemic - Karem Rouby Islam; Yanuar Luqman (Komunikator, 2022)
Health organizations, in this case, hospitals, have faced many difficult challenges due to the Covid- 19 pandemic, which forced them to change their working methods in order to adapt to the new circumstances. This study aimed to find out the tasks of the PR practitioner at RSND during the COVID-19 pandemic. The researchers used the qualitative method with a descriptive approach. The in-depth interview was used as a study tool to collect primary data. The researchers analyzed the data based on the main functions of public relations, chaos theory, and structural-functionalism theory. Meanwhile, the paradigm used in this study is the constructivism paradigm. The findings showed that the public relations officers at RSND developed their tasks in line with the new situation of the Coronavirus epidemic. Covid-19 imposed on the public relations officers several new tasks, most notably; coordination with Diponegoro University regarding complaints related to Coronavirus and the launch of RSND PCR laboratory services, electronic patient registration through RSNDku application, measuring patient satisfaction via the Internet, issuing awareness leaflets to the public about the dangers of Coronavirus and ways of prevention, interacting with hospital audiences through social media, in addition to several marketing, and other administrative duties. The uniqueness of PR in RSND during Covid-19 is launching Healthy Life MNC in collaboration with Trijaya 89.8 FM in Javanese and Indonesian language about Covid-19.